Online Larps in Japan (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2021)
This short note provides a brief, abridged overview of online larps and web-larps organized by Japanese larp organizations since 2019. Especially during the pandemic, many larpers in Japan experimented with online formats.